Acute effects of caffeine and paracetamol on velocity and power in resistance exercise - Scapec, Bela; Grgic, Jozo; Varovic, Dorian; Mikulic, Pavle (Frontiers in Physiology, 2025)
This study aimed to explore the isolated and combined effects of caffeine and paracetamol (acetaminophen) on velocity and power in resistance exercise. Twenty-eight resistance-trained men and women participated in this randomized, double-blind, placebo-controlled, crossover study. The participants performed three sets of the bench press with 75% of one-repetition maximum to momentary muscular failure after ingesting a placebo, caffeine (3 mg/kg), paracetamol (1,500 mg), or caffeine + paracetamol 45 min before exercise. Velocity and power of the repetitions in each set were analysed. Compared to placebo, only isolated caffeine ingestion increased mean velocity (d = 0.34), and mean power (d = 0.17) in the first set. No significant differences between the conditions were observed for any of the analysed outcomes in the second and third sets. Our results indicate that only isolated caffeine ingestion improves velocity and power in resistance exercise, even though these effects are not consistent across all sets. Paracetamol ingestion was not ergogenic, even when combined with caffeine. These results highlight that analgesics may be ineffective in improving resistance exercise performance.